ASSESSING GENETIC VARIATION OF PIGEONPEA [CAJANUS CAJAN (L.)] GENOTYPE USING RAPD AND ISSR MARKERS SYSTEMS - PRINCI RANI; ANIL SIROHI; A. K. PARIHAR; ANUBHA GUPTA (The Bioscan, 2015)
Pigeonpea is an important food legume being as a key ingredient of the human diet and imperative component of sustainable agriculture /cropping system. In present investigation 42 pigeonpea genotypes were evaluated for genetic relationship analysis using 10 random amplified polymorphic DNAs (RAPDs) and 10 inter simple sequences repeats (ISSRs)markers.Ten RAPDs primers generated 43 bands, of which 39 were found to be polymorphic. While in case of ISSR, 45 were observed to be polymorphic of the total 52 markers screened. Concerning DNA polymorphism detection, RAPD markers were found to be more efficient than the ISSR, as the former detected 90.6% compared to 86.5% for ISSR markers. Polymorphic information content (PIC) value of ISSR (7.67) was higher as compared to RAPD (7.29). Furthermore, Jaccard’s similarity coefficient obtained by pooled data revealed narrow range (0.71 to 0.93) among the studied genotypes. In the UPGMA based dendrogram the cluster analysis of RAPD and ISSR combined data revealed near similar clustering pattern. In this study we insight about the practical relevance of RAPD and ISSR based marker systems for understanding the genetic relationships in diverse pigeonpea genotypes.